Adapting to sea level rise: is India on- or off-track? - Puthucherril, Tony George (Frontiers in Marine Science, 2025)
Like many other regions worldwide, rising sea levels threaten to inundate India’s coastal zones and resources, potentially leaving millions impoverished and displaced. India is set to be among the countries severely impacted by climate change and rising sea levels. Fortunately, India has an adaptation strategy that could mitigate some of these effects and help prolong its resilience. This strategy integrates the tools available through its coastal law, hard and soft engineering measures, and nature-based adaptations. Additionally, India relies on Integrated Coastal Zone Management. This paper explores the challenges of rising seas and India’s responses to them. The primary argument is that the absence of coherent policies and laws integrating adaptation actions into a unified framework leads to suboptimal use of limited resources, frequently resulting in significant environmental issues, maladaptation and unsustainability.